TABOO WORDS USED BY THE CHARACTERS OF RESERVOIR DOGS MOVIE - RATNAFURI, FEBRINA RAHADIANTI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Communication is one of the most important things in our life because people can understand each other through communication. While communicating, they use a media called a language. Usually, people use a same language with different variation. Also, language as the communication media has avoidance which is known as taboo words (Wardhaugh, 2006). Those words are also the form of language variation, but not all the people use them in a conversation as often as the others. Some people only use it for a certain condition such as when they are angry, while some people undoubtedly use taboo words even in some works such as movies and songs. The example of taboo words in a movie can be seen in Reservoir Dogs movie. Therefore, this study is aimed to describe taboo words phenomena happen in a movie with several problems which are taboo words used by the characters in Reservoir Dogs movie, the types of taboo words used by them, and the context when the taboo words occurred. In conducting this research, the writer used descriptive qualitative method as well as document or content analysis approach. The writer also used sampling which is maximum variation sampling as one of the purposive sampling types. As the sample, the writer only took 21 utterances containing taboo words produced by Mr. White, and 20 of them produced by Nice Guy Eddie to describe the analysis on types of taboo words used as well as the context. In analyzing the type of taboo words, the writer used Wardhaugh’s (2006) theory. While for analyzing the context in which taboo words are occurred, the writer used Holmes’ (1992) theory which covers social factors such as participants, setting, topic, and function of taboo words. In this research, the writer finds 141 utterances containing taboo words, in which 71 utterances are uttered by Mr. White and 70 utterances are uttered by Nice Guy Eddie. The writer also concludes that the most occurrence type used by both characters is sex which is about 53%, which functions to give an emphasis and to express anger. The writer suggests for the next researcher to use more than one theory in analyzing the type of taboo word. The writer also suggests the next researchers who use movie as the object, to find different genre of the movie.   Keywords       : taboo words, types, context, social factors, Reservoir Dogs Movie, Mr. White, Nice Guy Eddie